Pengaruh Substitusi Kangkung Air (Ipomoea aquatica) Afkir Terfermentasi Terhadap Kualitas Fisik Daging Ayam Kampung Betina Super - Runesi, Evita C. Beti; Suryatni, Ni Putu F.; Theedens, Jonas F.; Armadianto, Heri (Animal Agricultura, 2024)
This research aims to determine the effect of substitution of fermented water spinach (Ipomoea aquatica) on the physical quality of meat from super female native chickens. This research used 80 super female free-range chickens aged 5-8 weeks. The research method used was a Complete Randomized Design (RAL) consisting of 4 treatments, each treatment consisted of 5 replication and each replication there were 4 chickens. The treatments in question include R0 = 100% commercial feed without substitution of fermented water spinach (control), R1 = 90% commercial feed + 10% fermented water spinach, R2 = 80% Commercial feed + 20% fermented water spinach, R3 = 70% Commercial feed + 30% fermented water spinach. The variables observed in this research were meat pH, water holding capacity, cooking loss, and tenderness. The results of this study showed that the treatment had no significant effect (P>0.05) on pH, Water Holding Capacity, Cooking Loss. However, it has a significant effect (P<0.05) on tenderness.Based on the results this research can be concluded that substitution of fermented water spinach give the same effect on pH, water holding, capacity cooking loss however the highest meat tenderness is at 10% substitution of fermented water spinach.